ANALASIS KEBUTUHAN PENGEMBANGAN MODEL PEMBELAJARAN PENDIDIKAN JASAMANI BERBASIS KECERDASAN MAJEMUK DI SEKOLAH DASAR - Gani, Ismail; Tomoliyus, Tomoliyus; Hariono, Awan; Rizkyanto, Willy Ihsan; Adji, Tito Pangesti (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the level of need for physical education teachers to develop multiple intelligence-based learning models at the elementary school level. This research is descriptive research with a quantitative approach. The sample in this study was 48 elementary school PJOK teacher respondents from five districts/cities in the DIY province who were obtained using a purposive sampling system. Data collection in this study was carried out using an instrument in the form of a questionnaire consisting of 15 statement items using a Likert scale of 1 – 5. Quantitative data analysis techniques were carried out using descriptive statistical tests with the help of SPSS software. The data obtained through the score of the questionnaire items are then converted into percentages and categories. The study results illustrate that the need for developing a physical education model based on multiple intelligences in DIY elementary schools is 87.00 and is in the very high category. The five factors of the learning model are included in the very high category, including the syntax factor of 87.63%, the social system factor of 81.11%, the principle of reaction of 85.97%, the support system of 87.39%, and the impact factor of instructional and accompaniment of 88.12%. These results need to be followed up for developing a multiple intelligence-based physical education learning model in elementary schools based on supporting theory, tested, and effective for implementation.